First results of multichord soft x-ray detection array on the U-3M torsatron - Dreval, M.B. (Вопросы атомной науки и техники, 2015)
A miniature pinhole camera array for spatially and temporally resolved measurements of soft X-ray plasma emission has been recently installed on the U-3M. The diagnostics has been tested in different types of the U-3M discharge. In low density frame antenna discharges with so-called “H-like” transition a fast SXR emission profile modification is observed. A phase shift of the SXR perturbation induced by the transition as well as different shapes of the perturbation is observed in different channels. The transition can be associated with MHD instability. Different shapes of the SXR emission profile has been observed in different discharge conditions. The SXR array is en excelent tool for study different types of the MHD activity. Different types of the low frequency MHD activity have been observed in the U-3M torsatron. The recently installed SXR diagnostics opens opportunity of detailed studies of the MHD activity together with its driver – the plasma pressure gradient. In the paper we are presented recent experimental results obtained with the use of SXP, without deep analysis these experiments. Миниатюрный датчик для измерения временного поведения и пространственного распределения излучения мягкого рентгена был недавно установлен на торсатроне У-3М. Диагностика протестирована в различных видах разряда У-3М. В низкоплотных разрядах рамочной антенны с так называемым переходом в Н-подобную моду обнаружена быстрая модификация профиля излучения мягкого рентгена. Сдвижка фазы возмущения излучения мягкого рентгена, вызванная переходом, а также различные формы возмущения наблюдались на различных каналах. Переход может быть ассоциирован с МГД-неустойчивостью. Различные формы профиля излучения мягкого рентгена наблюдались в различных условиях разряда. Многоканальный датчик мягкого рентгена - это превосходный инструмент для изучения различных типов МГД-активности. Различные типы низкочастотной МГД-активности наблюдались на торсатроне У-3М. Недавно установленная рентгеновская диагностика открывает возможность детального изучения МГД-активности вместе с вызывающей её причиной – градиентом давления плазмы. Представлены последние экспериментальные результаты, полученные с использованием диагностики мягкого рентгена, без глубокого анализа этих экспериментов. Мініатюрний датчик для вимірювання тимчасового поводження й просторового розподілу випромінювання м'якого рентгену був недавно встановлений на торсатроні У-3М. Діагностика протестована в різних видах розряду У-3М. У низькощільних розрядах рамкової антени з так званим переходом у Н-подібну моду виявлена швидка модифікація профілю випромінювання м'якого рентгену. Зрушення фази збурення випромінювання м'якого рентгену, що викликана переходом, а також різні форми збурення спостерігалися на різних каналах. Перехід може бути асоційований з МГД-нестійкістю. Різні форми профілю випромінювання м'якого рентгену спостерігалися в різних умовах розряду. Багатоканальний датчик м'якого рентгену- це чудовий інструмент для вивчення різних типів МГД-активності. Різні типи низькочастотної МГД-активності спостерігалися на торсатроні У-3М. Недавно встановлена рентгенівська діагностика відкриває можливість детального вивчення МГД-активності разом з причиною, яка її викликає - градієнтом тиску плазми. Представлені останні експериментальні результати, отримані з використанням діагностики м'якого рентгену, без глибокого аналізу цих експериментів.